Multinational Production: Effect on Brand Value - Johansson, Johny K.; Nebenzahl, Israel D. (Journal of International Business Studies, 1986)
Direct foreign investment in manufacturing abroad has a number of consequences for the firm. One aspect, particularly salient when the company's image is tied to its home country, is the impact of the DFI upon customer perceptions of the brand. The present study shows how changes in perceptions can be assessed prior to the investment decision, and how the brand value consequences of a particular location can be estimated. The proposed method is illustrated using data from a Japanese company's entry into the U.S.